The Avant-Guards. Volume two - Usdin, Carly (BOOM! Box, a division of Boom Entertainment, Inc., 2020)
"The Avant-Guards have been on a roll when it comes to their newly-formed basketball league, and Charlie has been getting more comfortable with her new teammates, but when they hit the end of their winning-streak, will these new friendships survive? As the Avant-Guards struggle to move forward, they'll soon learn just what it means to truly be a team--on the court and, most importantly, off the court, too."--Back cover